Pengaruh Market Rasio, Leverage, Ukuran Perusahaan, dan Likuiditas Terhadap Return Saham pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Yuana Jatu Nilawati; John Pieter Boantua (Ikatan Da'i Indonesia, 2026)
This study aims to examine The Effect Of Market Rasio, Leverage, Company Size, and Liquidity On Stock Returns In Manufacturing Companies In The Food and Beverage Sector Listed On The Indonesia Stock Exchange 2022-2024. This study uses secondary data obtained from annual reports and sustainability reports of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The sampling method used was purposive sampling, with a sample size of 57 companies over three years of observation, resulting in a total of 171 data points. Data analysis was conducted using a quantitative approach using EViews 12 through panel data regression analysis. The results show that financial performance, as measured by the market rasio, has no positive effect on stock returns. Solvency has a negative effect on stock returns. Company size has a positive effect on stock returns, and liquidity has a positive effect on stock returns.